DIGITALIZATION SYSTEM IN BUSINESS DEVELOPMENT EFFORTS FOR BREEDERS IN PRODUCER COOPERATIVES IN TAKALAR DISTRICT - Imran, S.T., M.Sc, Muhammad Alief Fahdal; Zainuddin, Zahir; Imran, Haliah; Hasan, Hasnawiyah; Wardihan, Fatmawati (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The INS Cooperative, which is located in Takalar Regency, South Sulawesi Province, has 11 MSMEs that collaborate with this cooperative. However, the low digital literacy of business actors in the INS Cooperative in managing and marketing their products means that the Cooperative's performance is less than optimal. The solution to overcome the problems faced is through modernization in terms of cooperative management to the concept of product marketing. The method used is a website-based information system modeling method and outreach and training to business actors, INS Cooperative managers and local communities who then carry out a survey. The survey was conducted with 11 business actors who are members of the INS Cooperative and 10 managers and communities who are members of the INS Cooperative to measure respondents' responses and to measure the level of success of the service carried out. As many as 76% of respondents initially did not understand the use of the cooperative website, but after socialization and training, 85% showed an increase in understanding of the use of the website. The level of difficulty in accessing information via the website also decreased significantly after the program was completed. The socialization and training carried out as a form of community service succeeded in increasing the digital literacy of business actors, the community and INS Cooperative managers, especially in using websites for cooperative operations. This program is also effective in reducing barriers to information access, significantly supporting the digital transformation of cooperatives.